The Traditions of the oriental archaeography in Kazan and Kazan University - Usmanova, Diliara; Mustafina, Dina (Slavistica Vilnensis, 2016)
This article is devoted to the history of the development and elaboration of the eastern archaeography in Kazan, which is addressed to the trace and study of oriental manuscripts in Arabic writing. It’s been revealed that archaeoraphical studies with far more than bicentenary tradition were discovered due to oriental studies in Kazan University. Also, the aforementioned studies were influenced by academicians’ gathering activity of Razryad vostochnoy slovesnosti and by Tatar enlighteners and intellectuals. The authors have closely examined an entirely new phase in the development of archaeographical studies, which took place in 60-s of the 20th century after regular archaeoraphical expeditions. Due to that, the number of manuscripts and black-letter books in the Science Library’s funds of Kazan University has dramatically increased. An establishment of Archaeographical laboratory turned out to be a logical continuation of previous expeditions that were oriented to the enlargement of cameralistic research, to the composition of inquiry publications and to the preparation of unique handwritten texts for printing. The authors of the above-named article have also defined perspectives of eastern archaeography’s development in Kazan University.